Triple Negative Receptor Status in Patients Diagnosed with Carcinoma Breast - Iram Bashir; Sheikh Qais Falah; Asif Shams (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To record frequency of triple negative receptor status in patients diagnosed with carcinoma breast. Methodology: This descriptive cross-sectional survey, was conducted at Surgical Unit III, Nishtar Hospital Multan, we included 171 females between 30-60 years of age diagnosed to have breast carcinoma on histopathology whereas those unfit to undergo surgical excision, established metastatic disease were excluded from the study. All these patients were undergo mastectomy by Consultant surgeon (having 5 years’ post-fellowship experience). All the specimens were sent to areference laboratory(Shaukat Khanam Memorial Trust Hospital) for immune staining for presence or absence of Esterogen receptor, Progesterone receptor and Her / neu receptor. Frequency was calculated for triple negativereceptor status (present/absent). Results: Total patients included in this study were 171 (100%) all were female. These 171 patients were divided into 3 groups, patients from 30-40 years included in group 1, age 41-50 included in group 2 and patients from 51-60 years included in group 3. According to age patients in which TNBC was present were have mean age 44.06 and standard deviation 9.107 similarly patients in which TNBC was absent were have mean age of 44.32 and standard deviation 8.953. According to TNBC patients of group 1 (30-40 years), 13 were have TNBC present and 53 were not, out of 55 patients of group 2 (41-50 years), 12 were have TNBC present and 43 were not, similarly out of 50 patients in group 3 (51-60), 10 were have TNBC present and 40 were not. Conclusion: Frequency of TNBC in patients of Carcinoma breast is 35% in our society.